2021
DOI: 10.1115/1.4049966
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Phase Modeling of the Powder Flow Dynamics and the Catchment Efficiency in Laser Directed Energy Deposition With Inclined Coaxial Nozzles

Abstract: Laser Directed Energy Deposition (DED) is one of the most promising additive manufacturing processes for restoring high value components. The damaged components can have complex free-form shapes which necessitates depositions with an inclined nozzle, where, the gravity can adversely affect the powder flow dynamics and the powder catchment efficiency (PCE). PCE is defined as the fraction of the total mass flow rate entering the melt pool and a low PCE can render the process inviable. In this paper, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Ahn et al [27] explored and deliberated upon the principles, optimization parameters, and practical applications, as explained in Figure 10, an electron beam is directed toward a plate or substrate material where it impinges with a wire or powder feedstock material and melts, leaving deposits of material on the bed. Further, in a study [28] Alya et al examined the effect of nozzle rotation on the dynamics of powder flow and the associated powder catchment efficiency, and the relation was discussed and examined from an energy point of view. It was found that an angled nozzle drastically changes the mechanics of the powder flow, producing an uneven and asymmetric powder jet, so it was proved that nozzle parameters are directly proportional to the parameters discussed.…”
Section: Direct Energy Deposition (Ded)mentioning
confidence: 99%
“…Ahn et al [27] explored and deliberated upon the principles, optimization parameters, and practical applications, as explained in Figure 10, an electron beam is directed toward a plate or substrate material where it impinges with a wire or powder feedstock material and melts, leaving deposits of material on the bed. Further, in a study [28] Alya et al examined the effect of nozzle rotation on the dynamics of powder flow and the associated powder catchment efficiency, and the relation was discussed and examined from an energy point of view. It was found that an angled nozzle drastically changes the mechanics of the powder flow, producing an uneven and asymmetric powder jet, so it was proved that nozzle parameters are directly proportional to the parameters discussed.…”
Section: Direct Energy Deposition (Ded)mentioning
confidence: 99%
“…The second type of LDED numerical model considers powder delivery and is recognized as a powder-scale model [18][19][20]. In this model, the powder handling approach can be categorized into two types based on the level of computational accuracy.…”
mentioning
confidence: 99%